Examining the effectiveness of entrepreneurial education types in enhancing students' entrepreneurial intention in Southwestern Nigeria - Adetola, Adelaja ayotunde (2019)
Entrepreneurship has been acknowledged to be among the viable ways to economic sustainability via youths’ engagements. In view of the potential benefits of entrepreneurship, several governments and agencies embark on entrepreneurial campaign. One of the major channels used is through entrepreneurial education. The reason for using this channel is, it is believed that through education, the intention of students towards entrepreneurship will be enhanced. However, ever since the adoption and implementation of entrepreneurial education curriculum in Nigeria as far back as early year 2000, lesser entrepreneurial activities are witnessed. This implies that there is less intention towards entrepreneurship among the students. Thus, the major objective of this research is to examine the effectiveness of entrepreneurial education in influencing students’ entrepreneurial intention in Nigeria. To achieve this, multistage sampling was adopted to classify Nigerian higher educations into clusters. At the end, a predesigned questionnaire was distributed undergraduate students who registered for entrepreneurial education twice. At the first stage, a simple random sample was used in selecting 532 students from the six federal universities located in the southwestern region in Nigeria. However, a total of 526 was valid for the data analysis. The Statistical Package for Social Science (SPSS) version 23 was used in analyzing the collected data. The analysis conducted includes, missing values, missing data, normality, Pairwise Sample-T test, Regression Analysis, ANOVA and Correlation analysis. The result presents that entrepreneurial education has a significant relationship with students’ entrepreneurial intention. Also, it was observed that the entrepreneurial education offered in Nigeria has an insignificant negative effect (comparing students’ entrepreneurial intention after and before exposure to entrepreneurial education). in addition, the findings reveal different effect of entrepreneurial education types on students’ entrepreneurial intention.